Morphology and Texture of Zinc Deposits Formed at the Edge of a Rotating Washer Electrode - Bengoa, Leandro Nicolás (2016)
In this paper, a rotating washer electrode was used to simulate the industrial conditions of strip edges during electrogalvanizing. Using this experimental setup, morphology and texture of the zinc deposits and dendrites formed at the edge of the electrode were studied. Dendrite precursors in the corner of the washer edge were well characterized and their nucleation and growth were also studied. The results indicated that the rotation speed has little effect on texture while, in contrast, current density modifies dendrites texture. It was found that dendrites are formed by platelets which are stacked on one another, which grow up in a series of steps oriented in the direction of growth of the dendrites stem yielding highly oriented structure. The presence of sodium ions in the electrolyte changes the morphology and shape of dendrites leading to rounded, cabbage-shaped crystals, while thiourea changes the morphology of both the deposit in the flat portion of the washer and the dendrites through adsorption on the zinc surface.